AKTIVITAS NITROGENASE BINTIL AKAR DAN KADAR KLOROFIL DAUN KACANG HIJAU {Phaseolus radiatus L.) PADA BERBAGAI JENIS DAN KADAR ASAM FENOLAT - Rauf, AWahid (BERITA BIOLOGI, 2008)
Phenolic acids are one of the many secondary metabolites causing toxic upon the growth and development of plant. Phenolic acids are produced by plant and subsequently released into soil, and appears to be involved in biochemical interaction between plants and other living organisms in soil. The research was conducted to study the effect of various kinds and doses of phenolic acids on nitrogenases activities and cholorophyll content of mungbean. Research was done in the glass house of Soil Science Departemen, Faculty of Agriculture, Gadjah Mada University (GMU) from April to June 2004. The experiment was arranged by randomized block design in three replications. The treatment consist of four kinds phenolic acid i.e. vanilic, p-coumaric, ferulic and p-1hydroxybenzoic with concentration at 250, 500, 1000 and 1500 mg kg-Ã respectively. One treatment was without phenolic acids as control. Result indicated that phenolic acids could reduce nitrogenases activities and chlorophyll content up to 53.35% and 29.98% respectively. The toxicity of p-hydroxybenzoic against both nitrogenases activities and chlorophyll content was higher than other phenolic acids.